2023
DOI: 10.1371/journal.pone.0289116
|View full text |Cite
|
Sign up to set email alerts
|

Parental knowledge and communication with their adolescent on sexual and reproductive health issues in Nepal

Abstract: Background Parental knowledge about sexual and reproductive health issues and adequate communication with their adolescent on these issues are crucial in promoting adolescent sexual and reproductive health. Although there are evidence on adolescent perceptions of their sexual health issues, research on parental perspectives of adolescent sexual health and parent-adolescent communication about sexual health issues in Nepal remains unexplored. Therefore, this study aimed to assess parental knowledge and communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This finding was in accordance with other previous studies conducted to evaluate the knowledge about SRH among parents and adolescents. A study conducted in Nepal in 2023 revealed that only one-third of parents had the correct knowledge about SRH 15 and according to a study conducted in 2020 in eight sites across sub-Saharan Africa by Finlay et al, many adolescents lacked knowledge about SHR except for the knowledge related to HIV. 16 The knowledge difference indicates that parents, guardians, and children are not discussing SRH.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in accordance with other previous studies conducted to evaluate the knowledge about SRH among parents and adolescents. A study conducted in Nepal in 2023 revealed that only one-third of parents had the correct knowledge about SRH 15 and according to a study conducted in 2020 in eight sites across sub-Saharan Africa by Finlay et al, many adolescents lacked knowledge about SHR except for the knowledge related to HIV. 16 The knowledge difference indicates that parents, guardians, and children are not discussing SRH.…”
Section: Discussionmentioning
confidence: 99%